Improving EFL ninth graders’ reading comprehension through thieves learning strategy - Yenny Asmarni; Wisma Yunita; Dedi Sofyan (Universitas Bengkulu, 2022)
Reading as a fundamental language skill become an essential skill in academic and social life. Especially at school, the teachers need to enrich the strategy in teaching and learning process. The objectives of this study were to find out 1) the improvement of students’ reading comprehension of the ninth grade (IXC) of SMPN 13 North Bengkulu, 2) some factors influence the change of students’ reading comprehension at the ninth grade (IX C) of SMPN 13 North Bengkulu. This Classroom Action Research (CAR) involved 25 students of the ninth grade of SMPN 13 North Bengkulu. Quantitative and qualitative data were employed to investigate the improvement of the students’ reading comprehension and the factors influence the changes of students’ reading comprehension. Reading comprehension test, observation checklists and field notes, and interview were the instruments of this research. Based on the test results, the percentage of students who had achieved the success criteria increased from 8% at the baseline to 80% at the end of the study. It can be concluded that applying Thieves strategy improved students’ reading comprehension and it was influenced by the student’s factors (attention, interest and participation) and the teacher’s factors (enriching the material and classroom management).